PFOS exposure at environmentally relevant concentrations promote papillary thyroid carcinoma progression through PI3K/AKT/mTOR-mediated epithelial-mesenchymal transition - Yaling Yu; Yi Wang; Xuling Su; Zhenzhen Cai; Qianqian Wang; Chenglong Wang; Yiwei Zhao; Tonghui Zhang; Danjie Hu; Zhiyan Liu (Environmental Research, 2026)

High-performance flexible organic field-effect transistor based on highly ordered poly(3-hexylthiophene) nanowires - Liangkun Lu; Meng Si; Shaobo Jin; Zirui Zhao; Xuling Liu; Liguo Dai; Yueming Zhou; Hongjie Yang; Guoyong Ye (Chemical Engineering Journal, 2025)

Map-based cloning revealed BhAPRR2 gene regulating the black peel formation of mature fruit in wax gourd (Benincasa hispida) - Xuling Zhai; Jinqiang Yan; Wenrui Liu; Zheng Li; Zhenqiang Cao; Ying Deng; Renlian Mo; Baochen Wang; Xiaoxin Cheng; Dasen Xie; Biao Jiang (Theoretical and Applied Genetics, 2025)

Comprehensive evaluation of hydrogen-rich energy application in iron ore sintering process: Deep function mechanism analysis and process optimization - Yufeng Wu; Xiaohui Fan; Zhiyun Ji; Min Gan; Dan Yu; Zengqing Sun; Xuling Chen; Lincheng Liu; Xiaoxian Huang; Jinhua Li (Journal of Cleaner Production, 2023)

Threat of soil formation rate to health of karst ecosystem - Chen Ran; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Yue Cao; Luhua Wu; Fei Chen; Chaojun Li; Xuling Luo; Min Liu; Sirui Zhang (Science of The Total Environment, 2023)

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes - Chaojun Li; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Luhua Wu; Fei Chen; Huipeng Xi; Xuling Luo; Chen Ran; Huan Chen; Sirui Zhang; Min Liu; et al. (Global Change Biology, 2022)
Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO 2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSF α ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSF α . We found that the total SCSF α was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSF α in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSF α was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSF α to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle.

Telephone Follow-up Design and Practice for Advanced Cancer Pain Patients - Benyan Zou; Xuling Li; Xuxia Huang; Dandan Xiong; Yu Liu (Journal of Cancer Education, 2020)

The effects of Japanese encephalitis virus antibodies on Zika virus infection - Xiaoen He; Xinyue Lang; Jianhai Yu; Li Zhu; Zhiran Qin; Xuling Liu; Pei Chen; Chengguqiu Dai; Tingting Chen; Xujuan Li; Yangyang Chen; Dongrui Zhou; et al. (Medical Microbiology and Immunology, 2020)

Characteristics and complete genome sequence of the virulent Vibrio alginolyticus phage VAP7, isolated in Hainan, China - Mingming Gao; Yanhong Qin; Hang Fan; Xianglilan Zhang; Puyuan Li; Huiying Liu; Guangqian Pei; Zhiqiang Mi; Xuling Xu; Yigang Tong; Changqing Bai (Archives of Virology, 2020)

CLU rs9331888 Polymorphism Contributes to Alzheimer’s Disease Susceptibility in Caucasian But Not East Asian Populations - Shuyan Zhang; Xuling Li; Guoda Ma; Yongshuai Jiang; Mingzhi Liao; Rennan Feng; Liangcai Zhang; Jiafeng Liu; Guangyu Wang; Bin Zhao; Qinghua Jiang; Keshen Li; et al. (Molecular Neurobiology, 2016)

Estimation on aesthetic value of tourist landscapes in a natural heritage site: Kanas National Nature Reserve, Xinjiang, China - Feng Di; Zhaoping Yang; Xuling Liu; Jingrui Wu; Zhongguo Ma (Chinese Geographical Science, 2010)

Evaluation on tourism ecological security in nature heritage sites —Case of Kanas nature reserve of Xinjiang, China - Xuling Liu; Zhaoping Yang; Feng Di; Xuegang Chen (Chinese Geographical Science, 2009)

Empirical analysis of Xinjiang’s bilateral trade: Gravity model approach - Xuegang Chen; Zhaoping Yang; Xuling Liu (Chinese Geographical Science, 2008)